2006
DOI: 10.1095/biolreprod.106.053264
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure of Female Sheep to Physiologic Concentrations of Estradiol: Effects on the Onset and Maintenance of Reproductive Function, Pregnancy, and Social Development in Female Offspring1

Abstract: As steroids and steroid-like compounds accumulate in the environment, it has become important to understand how low-dose exposure affects reproductive function. Ovary-intact sheep were used in a multigenerational study, to determine whether chronic exposure to low levels of estrogen disrupts reproductive function and behavior. We assessed parameters of reproductive performance in control and postnatally estradiol-treated females (Generation 1, G1), and their offspring (Generation 2, G2). In the G1 animals, 17b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…Diminished gonadotropin release in response to E positive feedback was observed in prepubertal female sheep chronically treated with E in this study and in previous studies (Malcolm et al 2006). However, a reduction in periovulatory release of gonadotropins was not observed when examined during the first and second breeding season.…”
Section: Discussionsupporting
confidence: 85%
“…Diminished gonadotropin release in response to E positive feedback was observed in prepubertal female sheep chronically treated with E in this study and in previous studies (Malcolm et al 2006). However, a reduction in periovulatory release of gonadotropins was not observed when examined during the first and second breeding season.…”
Section: Discussionsupporting
confidence: 85%
“…That LH surge responses normalize with reproductive maturity is also supported by our finding in ovariectomized prenatally BPA-treated females at 21 months of age, which showed a normal LH response to an exogenous estradiol administration (Abi Salloum et al, 2013). A similar outcome was achieved with prenatal estradiol treated sheep, namely reduction in LH surge amplitude when tested at 3.5 months of age, but not at 12 months of age (Malcolm et al, 2006). …”
Section: Discussionsupporting
confidence: 56%
“…0.46 cm; sealed with Silastic adhesive Type A, Dow-Corning Corp., Midland, MI) packed with crystalline 17β-estradiol (Sigma, St. Louis, MO) between days 30 – 90 of gestation. Past research revealed that the females receiving a lower dose of prenatal 17β-estradiol (13-mm silastic implant throughout the pregnancy) demonstrated an increase in aggressive displacement behavior as lambs and altered LH-surge properties prepubertally, but had a normal onset of puberty, normal postpubertal LH characteristics, and normal female-typical mating behavior (Malcolm et al, 2006). Because this estradiol-treated group consisted of only two animals, their data will be shown for completeness, but no statistical analyses will be reported.…”
Section: Methodsmentioning
confidence: 99%